Update in Geriatrics - Amornyotin, Somchai (IntechOpen, 2021)
Geriatric is a topic of great interest in medicine and among the general public. Population aging is an inevitable and irreversible demographic reality that is associated with welcome improvements in health care. The increase in life expectancy has led the very old to become the fastest-growing segment. The geriatric population experiences significant alterations of numerous organ systems as a result of the aging process. Normally, functional reserve and organ functions are declined in geriatric patients. The care of geriatric patients can be complex and will be a growing task. A balance between physiological and psychological alterations is required in these patients. Geriatric patients also have several co-morbidities including hypertension, cardiac disease, diabetes, cerebrovascular disease, and renal dysfunction.